Analysis of Radio Science Data from the KaT Instrument of the 3GM Experiment During JUICE’s Early Cruise Phase - Paolo Cappuccio; Andrea Sesta; Mauro Di Benedetto; Daniele Durante; Umberto De Filippis; Ivan di Stefano; Luciano Iess; Ruaraidh Mackenzie; Bernard Godard (Aerospace)
The JUpiter Icy Moon Explorer (JUICE) mission, launched on 14 April 2023, aims to explore Jupiter and its Galilean moons, with arrival in the Jovian system planned for mid-2031. One of the scientific investigations is the Geodesy and Geophysics of Jupiter and the Galilean Moons (3GM) radio science experiment, designed to study the interior structures of Europa, Callisto, and Ganymede and the atmospheres of Jupiter and the Galilean moons. The 3GM experiment employs a Ka-band Transponder (KaT) to enable two-way coherent range and Doppler measurements used for the gravity experiment and an Ultra Stable Oscillator (USO) for one-way downlink occultation experiments. This paper analyzes KaT data collected at the ESA/ESTRACK ground station in Malargüe, Argentina, during the Near-Earth Commissioning Phase (NECP) in May 2023 and the first in-cruise payload checkout (PC01) in January 2024. The radiometric data were fitted using both NASA’s Mission Analysis, Operations, and Navigation Toolkit Environment (MONTE) and ESA’s General Orbit Determination and Optimization Toolkit (GODOT) software. The comparison of the orbital solutions showed an excellent agreement. In addition, the Doppler and range residuals allowed a preliminary assessment of the quality of the radiometric measurements. During the NECP pass, the radio link data showed a range-rate noise of 0.012 mm/s at 1000 s integration time, while the root mean square of the range residuals sampled at 1 s was 8.4 mm. During the first payload checkout, the signal power at the KaT input closely matched the value expected at Jupiter, due to a specific ground station setup. This provided early indications of the 3GM’s performance during the Jovian phase. In this test, the accuracy of range data at an integration time of 1s, particularly sensitive to the link signal-to-noise ratio, degraded to 13.6 cm, whilst the range-rate accuracy turned out to be better than 0.003 mm/s at 1000 s, thanks to the accurate tropospheric delay calibration system (TDCS) available at the Malargue station (inactive during NECP).